Older Adults Newly Diagnosed with Symptomatic Myeloma Want to Participate in Treatment Decision Making - Tariman, Joseph D. (2014)
PURPOSE/OBJECTIVES: The purpose of the study was to describe the preferences for participation in decision making of older patients newly diagnosed with symptomatic myeloma and to explore the association between sociodemographic variables and decisional role preferences. DESIGN: Descriptive, cross sectional design SETTING: Subjects’ homes and two large academic cancer centers. SAMPLE: The convenience sample consisted of 20 older adults (60 years of age and above) with symptomatic myeloma diagnosed within the past 6 months. METHODS: The Control Preferences Scale was administered followed by an in-person one-time semi-structured interview. MAIN RESEARCH VARIABLES: Role preferences for participation in treatment decision-making, age, gender, race, work status, personal relationship status, education, and income. FINDINGS: 55% (n=11) of the subjects had preferred a shared role with the physician and 40% (n=8) had preferred to make the decisions after seriously considering the opinion of their physicians. Only one subject preferred to leave the decision to the doctor as long as the doctor considered the patient’s treatment preferences. Sociodemographic characteristics had no impact on preferences for participation in treatment decision-making. CONCLUSIONS: The study findings indicate that older adults newly diagnosed with myeloma wanted to participate during treatment decision-making. Oncology nurses must respect the patient's desired role preference and oncology clinicians must listen to the patient and allow them to be autonomous in making treatment decisions if the patient so desire such control in the decision-making process. A culture of equipoise between the patient and the clinician during TDM must be cultivated in order to achieve the patient's desired level of participation. More studies that focus on supporting and involving patients diagnosed with myeloma in the decision-making process are needed in order to influence clinical practice and policy. PRACTICE IMPLICATIONS: Nurses and other oncology clinicians can elicit patient’s preferred level of participation in treatment decision-making. Oncology nurses can do the following nursing actions: make sure patients receive disease and treatment-related information; encourage patients to express their decisional role preference to the physician; develop a culture of mutual respect and value the patient's desire for autonomy for treatment decision making; acknowledge that the right to make a treatment choice belongs to the patient; 5) provide psychological support to the patient during treatment decision making throughout the care continuum.